Structural Diversity and Changes in Conformational Equilibria of Biantennary Complex-Type N-Glycans in Water Revealed by Replica-Exchange Molecular Dynamics Simulation - Re, Suyong (The Biophysical Society, 2011)
Structural diversity of N-glycans is essential for specific binding to their receptor proteins. To gain insights into structural and dynamic aspects in atomic detail not normally accessible by experiment, we here perform extensive molecular-dynamics simulations of N-glycans in solution using the replica-exchange method. The simulations show that five distinct conformers exist in solution for the N-glycans with and without bisecting GlcNAc. Importantly, the population sizes of three of the conformers are drastically reduced upon the introduction of bisecting GlcNAc. This is caused by a local hydrogen-bond rearrangement proximal to the bisecting GlcNAc. These simulations show that an N-glycan modification like the bisecting GlcNAc selects a certain “key” (or group of “keys”) within the framework of the “bunch of keys” mechanism. Hence, the range of specific glycan-protein interactions and affinity changes need to be understood in terms of the structural diversity of glycans and the alteration of conformational equilibria by core modification.